(untitled) (Bangladesh Journal of Medical Science, 2023)
Aim: of this study was to assess and compare, the radiopacity of nanoparticle-based (NPB) root canal sealers with Epoxy Resin Based(ERB) root canal sealer using an aluminium step wedge in accordance with ISO 6876/2012 standards. Materials and methods: The specimens, which were made of each sealer material, had a 10mm diameter and a 1mm thickness. The creation of metallic matrices, which were used in the fabrication of the impressions, was done using a light-bodied silicone-based impression medium. Using an aluminium step-wedge, the radiopacity of the NPB sealer and the ERB sealer was assessed in accordance with international standards. The optical density was measured using a sample of enamel, dentin, and aluminium of the appropriate thickness, all measuring 1 mm thick. Results: The radiopacity of the ERB sealer was 2.37, with a minimum value of 179 and a maximum value of 215. The radiopacity value for the NPB sealer was 3.47, with a minimum value of 185 and a maximum value of 255. Conclusion: Within the limits of the study, the NPB root canal sealers has better radiopacity than the ERB sealers. It has radiopacity values of the sealers are within the ADA/ISO recommendations. Clinical Significance: The radiopacity of the NPB sealer can be compared with other commercially available sealers for in vivo applications. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.63-66